A minireview on the bioinformatics analysis of mobile gene elements in microbiome research - Schwarzerova, Jana; Labanava, Anastasiya; Rychlik, Ivan; Varga, Margaret; Cejkova, Darina (Frontiers in Bacteriology, 2023)
The horizontal transfer of mobile gene elements between bacteria plays a crucial role in their evolutionary dynamics. Additionally, it enables the accumulation and dissemination of genes conferring antibiotic and heavy-metal resistance, and thus contributes to the worldwide emergence and spread of drug-resistance pathogens. This process is instrumental in maintaining genetic diversity within bacterial populations and facilitates their adaptation to novel environments. It allows bacteria to acquire genes responsible for the synthesis of enzymes that utilize alternative energy sources and substrates. Furthermore, bacteria can acquire genes associated with toxin production and increased virulence.Horizontal gene transfer serves as a pivotal mechanism in bacterial evolution, enabling the acquisition of novel genetic information and enhancing their capabilities. However, the proper detection and identification of horizontally transferred genes at the microbiome scale is challenging, whether using wet-lab experiments or bioinformatics approaches. In the paper, we summarize current bioinformatics tools for detecting Horizontal Gene Transfer and present the results of our bioinformatic analysis on a collection of genomes originating from chicken gut microbiota.